PENGARUH MORALITAS INDIVIDU DAN PENGENDALIAN INTERNAL TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Empiris Pada SKPD di Kota Padang) - Eliza, Yulina (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2015)
This study aims to prove empirically: How much influence individual morality to thetendency of accounting fraud and how much influence the internal control overaccounting fraud tendencies. The sample was working units (SKPD) Padang city of48 agencies consist of: Secretariat, Department, Agency, Office, and the District inthe city of Padang. Data were collected by distributing questionnaires to therespondents, while the analysis method used is multiple linear regression method.Results of this study indicate that individual morality turns negative and significanteffect on the rate of Accounting Fraud Trends in Padang city SKPD. That is thebetter individual morality hence diminishing the level of accounting fraud.Furthermore, the Internal Control System and significant negative effect on the levelof the tendency of cheating accounting SKPD Padang. This influence is negative,which means more effective system of internal control then the trend rate ofAccounting fraud on the wane.Keywords: Morality, fraud, accounting